Visual Explorer Facilitator's Guide. - Palus, Charles J. (Center for Creative Leadership, 2010)
Grounded in research and practice, the Visual Explorer"!Facilitator's Guide provides a method for supporting collaborative, creative conversations about complex issues through the power of images. The guide is available as a component in the Visual Explorer Facilitator's Letter-sized Set, Visual Explorer Facilitator's Post card-sized Set, Visual Explorer Playing Card-sized Set, and is also available as a stand-alone title for purchase to assist multiple tool users in an organization